The effects of pulse repetition rate on the structural, surface morphological and UV photodetection properties of pulsed laser deposited Mg-doped ZnO nanorods. Issue 6 (1st May 2016) - Shewale, P.S.; Yu, Y.S.
Abstract: The Mg0.05 Zn0.95 O (MZO) nanorod array (NRA) films have been successfully grown onto SiO2 / n-Si substrates by pulsed laser deposition (PLD) without any template or seed layer and the influence of pulse repetition rate (3 to 15 Hz) of a 248 nm KrF excimer laser on their crystallinity, surface morphology and UV photodetection properties were systematically investigated. All the samples show the hexagonal wurtzite phase with a preferential c -axis orientation and the optimum crystallization of the MZO NRAs occurs at 5 Hz. FE-SEM analysis revealed that the growth of MZO NRAs is strongly influenced by the pulse repetition rate. It was observed that the average film thickness increases almost linearly with the pulse repetition rate and the MZO nanorod arrays grown at 5 Hz exhibits best surface area. Moreover, the room temperature UV photodetection properties of the samples were investigated in metal–semiconductor–metal (MSM) planar configurations and are found to be strongly driven by the pulse repetition rate dependent crystalline and surface morphological features. The device current–voltage ( I – V ) characteristics were measured under dark and UV light conditions. Then, the photocurrent and responsivity were measured with the variation of optical power density and applied voltage, respectively. Transient photoresponse studies show an exceedingly stable and fast switching UV photoresponse for the photodetector having MZO nanorods grown at 5 Hz, which demonstrates highest responsivity of 17 mA/W upon 2 mW/cm 2 UV illumination (365 nm), at 5 V bias.